2020
DOI: 10.1111/ijcp.13623
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short‐term xylitol chewing gum on pro‐inflammatory cytokines andStreptococcus mutans: A randomised, placebo‐controlled trial

Abstract: Introduction Dental caries is an infectious disease with predominantly of cariogenic bacteria such as Streptococcus mutans (S mutans). Xylitol is considered as one of the effective agents that can limit this dental infection. In this randomised, placebo‐controlled trial, we aimed to evaluate the potential reflection of short‐term xylitol consumption on pro‐inflammatory cytokines (TNF‐α, IL‐6 and IL‐8) and S mutans counts by ELISA and qPCR (Quantitative real‐time PCR), respectively. Methods In this study, 154 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…All studies included in the review were prospective, randomized, controlled studies published between 1971 and 2020 [38][39][40][41][42][43][44][45][46][47][48][49][50][51]. In the 16 studies included in the review, all participants were classified as healthy by the authors of the studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies included in the review were prospective, randomized, controlled studies published between 1971 and 2020 [38][39][40][41][42][43][44][45][46][47][48][49][50][51]. In the 16 studies included in the review, all participants were classified as healthy by the authors of the studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In one study, the primary outcome measure was the acidogenicity of plaque [49], and in another, caries occurrence [48]. In one of the studies, the stimulated saliva flow rate was the primary outcome measure [47], in one, bleeding on marginal probing [50], and in one, pro-inflammatory cytokines [51]. had a low risk of bias [46,47], two studies [49,50] were scored as having a high risk of bias, and the rest (12 studies) had an unclear risk of bias.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we have identified two candidate agents with potential activity against SARS-CoV-2 which can be administered intranasally, namely, xylitol and grape seed fruit extract (GSE). Xylitol, a sweetener with antimicrobial and anti-inflammatory properties, has been shown effective in decreasing the incidence of dental caries and improving chronic rhinitis as well as important microbiota and immunological modulatory effects (Akgül et al, 2020; Haukioja et al, 2008; Weissman et al, 2011; Xu et al, 2016). Xylitol has been reported to have multiple health benefits as well as is generally safe and well-tolerated for most adults in doses up to 35 grams per day and up to 20 grams per day in children (Salli et al, 2019; Storey et al, 2007; Ur-Rehman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%